Maternal Calorie Restriction Induces a Transcriptional Cytoprotective Response in Embryonic Liver Partially Dependent on Nrf2 - George I. Habeos; Fotini Filippopoulou; Evagelia E. Habeos; Electra Kalaitzopoulou; Marianna Skipitari; Polyxeni Papadea; George Lagoumintzis; Athanasios Niarchos; Christos D. Georgiou; Dionysios V. Chartoumpekis (MDPI AG, 2022)
Background: Calorie restriction is known to enhance Nrf2 signaling and longevity in adult mice, partially by reducing reactive oxygen species, but calorie restriction during pregnancy leads to intrauterine growth retardation. The latter is associated with fetal reprogramming leading to increased incidence of obesity, metabolic syndrome and diabetes in adult life. Transcription factor Nrf2 is a central regulator of the antioxidant response and its crosstalk with metabolic pathways is emerging. We hypothesized that the Nrf2 pathway is induced in embryos during calorie restriction in pregnant mothers. Methods: From gestational day 10 up to day 16, 50% of the necessary mouse diet was provided to Nrf2 heterozygous pregnant females with fathers being of the same genotype. Embryos were harvested at the end of gestational day 16 and fetal liver was used for qRT-PCR and assessment of oxidative stress (OS). Results: Intrauterine calorie restriction led to upregulation of mRNA expression of antioxidant genes (Nqo1, Gsta1, Gsta4) and of genes related to integrated stress response (Chac1, Ddit3) in WT embryos. The expression of a key gluconeogenic (G6pase) and two lipogenic genes (Acacb, Fasn) was repressed in calorie-restricted embryos. In Nrf2 knockout embryos, the induction of Nqo1 and Gsta1 genes was abrogated while that of Gsta4 was preserved, indicating an at least partially Nrf2-dependent induction of antioxidant genes after in utero calorie restriction. Measures of OS showed no difference (superoxide radical and malondialdehyde) or a small decrease (thiobarbituric reactive substances) in calorie-restricted WT embryos. Conclusions: Calorie restriction during pregnancy elicits the transcriptional induction of cytoprotective/antioxidant genes in the fetal liver, which is at least partially Nrf2-dependent, with a physiological significance that warrants further investigation.